"You Don't Want to Feel Poor All the Time": What SNAP Means to Low-Income Philadelphia Residents. (June 2021) - Brown, Keith R.; Hanlon, Colette; Scola, Becki
Through participant observation while grocery shopping, and 37 in-depth interviews with Supplemental Nutrition Assistance Program (SNAP) recipients, we describe the social meanings of SNAP dollars to low-income Philadelphia residents. We make three contributions to the study of food insecurity and SNAP. First, we confirm the literature showing that SNAP covers less than half of a monthly food budget. Second, we apply the "social meaning of money" theory to show that our respondents did not equate or spend SNAP dollars the same way they spent other forms of money. Spending SNAP dollars allowed for a temporary escape from the stresses of poverty. And third, we describe the cultural capital (habits and shared meanings) that is necessary to feed a family on a limited budget. In the SNAP market, the cultural capital accumulated through poverty is more valuable than the cultural capital obtained through wealth. Thus, we push for a more nuanced understanding of cultural capital among poverty scholars that keeps the focus on the contextual and interactional nature of this concept.